1993
DOI: 10.1111/j.1752-1688.1993.tb03206.x
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMIC EVALUATION OF AESTHETIC AMENITIES: A CASE STUDY OF RIVER VIEW1

Abstract: Presence of a river in an urban setting may contribute positively to an aesthetically pleasing environment. Such aesthetic effects are not typically linked to specific economic activities and occur, for example, when residents are exposed to a river‐view. Qualities enhancing the aesthetic value of the river include the presence of parks, trails, and vegetation along the riverbanks. The value of aesthetic amenities provided by the South Saskatchewan to the City of Saskatoon residents was estimated in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Some studies also evaluate the influence of water quality on property value in addition to shorefront and proximity (d'Arge and Shogren 1989;David 1968;Feather, Pettit, and Ventikos 1992;Young and Teti 1984); improved water quality increases property values. Other applications of the hedonic property price method for valuing water resources include reservoir level changes (Khairi-Chetri and Hite 1990), river views (Kulshreshtha and Gillies 1993), and restoration of urban streams (Streiner and Loomis 1995).…”
Section: Property Price Methods In Water Resources Valuationmentioning
confidence: 99%
“…Some studies also evaluate the influence of water quality on property value in addition to shorefront and proximity (d'Arge and Shogren 1989;David 1968;Feather, Pettit, and Ventikos 1992;Young and Teti 1984); improved water quality increases property values. Other applications of the hedonic property price method for valuing water resources include reservoir level changes (Khairi-Chetri and Hite 1990), river views (Kulshreshtha and Gillies 1993), and restoration of urban streams (Streiner and Loomis 1995).…”
Section: Property Price Methods In Water Resources Valuationmentioning
confidence: 99%
“…Previous studies have shown that proximity to shoreline is highly desirable in residential housing markets (Shabman and Bertelson 1979;Milon, Gressel, and Mulkey 1984;Earnhart 2001;Landry, Keeler, and Kriesel 2003). The literature suggests that residential properties with water views command a price premium (Kulshreshtha and Gillies 1993;Lansford and Jones 1995;Bin et al 2008), but the premium is influenced by the quality of amenities provided by the water body in addition to the quality of the view (Streiner and Loomis 1995;Benson et al 1998). Leggett and Bockstael (2000) use hedonic techniques to show that water quality has a significant effect on property values along the Chesapeake Bay.…”
Section: Effect Of Riparian Buffers On Residential Property Valuesmentioning
confidence: 96%
“…This interpretation is also supported by the fact that residential and recreational df -degree of freedom; for abbreviations see Table 1 doi: 10.17221/11/2016-SWR houses also are more strongly in demand in the vicinity of rivers and command higher prices than do more distant properties (Kulshreshtha & Gillies 1993). The natural character of the river and its surroundings also plays an important role, as shown by the study of Mooney and Eisgruber (2001).…”
Section: Proximity To Water Features and Other Factorsmentioning
confidence: 89%